Authentic vs. Servant Leadership and Generation Z Employee Engagement in the Indonesian Hospitality Industry: A JD-R and SET Perspective - Alisha Mohammad Imraan; Muhammad Hamdi (Manunggal Halim Jaya, 2026)
This study examines the effects of authentic leadership and servant leadership on employee engagement among Generation Z employees in the Indonesian hospitality sector, with job satisfaction serving as a mediating mechanism. Drawing on the Job Demands–Resources (JD-R) model and Social Exchange Theory (SET), this study argues that authentic leadership functions as a psychological job resource, while servant leadership operates as a social and developmental resource that shapes employees’ work attitudes. A purposive sample of 206 frontline Generation Z hospitality employees in Yogyakarta, Indonesia, was collected through a structured self-administered questionnaire. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with bootstrapping techniques. The results indicate that authentic leadership positively affects employee engagement (β = 0.399, t = 2.943, p = 0.003) and job satisfaction (β = 0.433, t = 2.769, p = 0.006). Servant leadership significantly affects job satisfaction (β = 0.500, t = 3.172, p = 0.002), but its direct effect on employee engagement is not significant (β = 0.212, t = 1.507, p = 0.132). Job satisfaction also positively influences employee engagement (β = 0.335, t = 2.637, p = 0.008) and mediates the relationships between both leadership styles and employee engagement. These findings suggest that authentic leadership directly strengthens employee engagement, whereas servant leadership enhances engagement primarily through increased job satisfaction. This study contributes to the leadership and hospitality literature by clarifying the distinct motivational pathways through which values-based leadership supports Generation Z employee engagement.